2021
DOI: 10.3390/atmos12060692
|View full text |Cite
|
Sign up to set email alerts
|

Major Floods and Tropical Cyclones over Bangladesh: Clustering from ENSO Timescales

Abstract: The present study analyzed major floods and tropical cyclones (TCs) over Bangladesh on El Niño-Southern Oscillation (ENSO) timescales. The geographical location, low and almost flat topography have introduced Bangladesh as one of the most vulnerable countries of the world. Bangladesh is highly vulnerable to the extreme hazard events like floods and cyclones which are impacted by ENSO. ENSO is mainly a tropical event, but its impact is global. El Niño (La Niña) represents the warm (cold) phase of the ENSO cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Interestingly, the highest SLAs were observed in May (Figure 10a), and the difference in R 2 for these events was generally small. We confirmed that these events mostly occurred in early May in 1995 and 1997, and there were tropical cyclones or tropical depressions over the study area [59,60]. Hence, it is very likely that these ESL events were strongly influenced by SLP and winds, rather than the precipitation effect.…”
Section: Seasonal Variations Of the Impact Of Precipitationsupporting
confidence: 73%
See 1 more Smart Citation
“…Interestingly, the highest SLAs were observed in May (Figure 10a), and the difference in R 2 for these events was generally small. We confirmed that these events mostly occurred in early May in 1995 and 1997, and there were tropical cyclones or tropical depressions over the study area [59,60]. Hence, it is very likely that these ESL events were strongly influenced by SLP and winds, rather than the precipitation effect.…”
Section: Seasonal Variations Of the Impact Of Precipitationsupporting
confidence: 73%
“…It was found that the ESLs were influenced by the high precipitation during the monsoon season. The extreme sea levels intensify coastal inundation and cause coastal floods with high precipitation during monsoons [8,32,57,59,65]. Therefore, the attempt of this study relating to predictions of ESL has implications for the reduction of coastal hazards.…”
Section: Discussionmentioning
confidence: 99%
“…A generalized additive model (GAM) is a powerful and simple technique and easy to interpret based on the flexibility and regularization of prediction functions [32][33][34][35][36][37] Modeling studies will be a great societal value when the risk-mitigation policies are considered and future planning efforts are focused to the most high-risk areas [38][39][40][41][42]. In the present study, we have used a kernel density estimation approach and GAM to observe the typhoon characteristics in the WNP basin.…”
Section: Introductionmentioning
confidence: 99%
“…Atmosphere 2021, 12,1446 2 of 20 In recent years, a lot of research has been conducted to detect the possible relation between large-scale climate phenomena and droughts or floods in specific geographical locations [2,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Wahiduzzaman concluded that major flood events over Bangladesh occurred during the monsoon period, and most of them occurred under the La Niña condition [24]. Sobral et al detected the relation between the annual SPI index and the El Niño-Southern Oscillation (ENSO), and found that the events of El Niño and La Niña were not directly related to the variation in rainfall in any region of South Rio de Janeiro (SRJ) [25].…”
Section: Introductionmentioning
confidence: 99%